PENGARUH PEMBERIAN TUGAS DAN MOTIVASI BELAJAR TERHADAP TANGGUNG JAWAB MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI - Paijan Rambe; Annisa Rahmadani; Yulia Novita (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The character development of young people is mandated by law. One of the characteristics that is missing is a responsibility that is now lacking in the current generation of young people. The provision of tasks and learning motivation is one solution. The purpose of this study is to analyze the effect of assignment and learning motivation on the responsibility of students in the economic education study program. This research is a survey research type with quantitative methods and a correlational design. The subjects of this study were 54 students in the economic education study program who were randomly chosen. The data collection technique is a questionnaire, while the data analysis technique is a partial t test and a simultaneous F test. The results stated that giving partial assignments to students greatly affected their responsibilities in life by 57.9%, but motivating student learning did not affect them partially, only 0.8%. The assignment and motivation of students to study simultaneously still affect their responsibilities by 58.7%. Â Â Keywords:Â Assignment, Learning motivation, Responsibility.